Toll-Like Receptor 3-4 Expression Decrease in BALB/c Diabetic Mouse Models - Muhaimin Rifa’i; Aris Soewondo; M. Sasmito Djati (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
In  this  study, we observed the effect of propolis  extract on immunological function in diabetic mouse models with the aim of highlighting the dynamics of immunological status in type-2 diabetes. In this study we tested the ability of propolis to normalize homeostasis. Here we showed that propolis improve homeostasis by slightly increasing the level of TLR expression. The results of this study differ from previous findings which reported that TLR expression increased in diabetes mellitus and most treatment is intended to suppress the expression of TLR. In this study we found that TLR-3 and TLR-4 expression decreased in mouse models of STZ induced diabetes mellitus. Furthermore, we found that administration of propolis showed an increase of red blood cell precursors (TER-119) and improve the ratio of CD4:CD8 dependent manner.